2019
DOI: 10.1007/s40204-019-0111-z
|View full text |Cite
|
Sign up to set email alerts
|

Cold atmospheric plasma as a promising approach for gelatin immobilization on poly(ε-caprolactone) electrospun scaffolds

Abstract: Poly(Ɛ-caprolactone) (PCL) is a biocompatible polymer with a high potential to be used in tissue engineering especially in tight tissues. In the current study, cold atmospheric plasma (CAP) is used as a promising method for immobilization of gelatin as a functional biomacromolecule on PCL nanofibrous substrates. The CAP surface modification leads to oxidation of chemical groups existing on the PCL surface without doing any damage to the bulk properties of biomaterials for gelatin biomacromolecule grafting. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 37 publications
1
26
0
Order By: Relevance
“…One of the exciting solutions to this problem is to combine this scaffold with another natural polymer Here, CAP treatment on the PCL surface was used to graft CMC. Through CAP, rebuilding the microstructures and modifying the surface properties of the scaffolds became possible [17,20] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the exciting solutions to this problem is to combine this scaffold with another natural polymer Here, CAP treatment on the PCL surface was used to graft CMC. Through CAP, rebuilding the microstructures and modifying the surface properties of the scaffolds became possible [17,20] .…”
Section: Discussionmentioning
confidence: 99%
“…The CAP added oxygen-containing groups like carboxyl, which resulted in a higher hydrophilicity and surface enhancement for grafting. Consequently, wettability and coloniality by cells were improved [20,27] . Bak et al [27] have demonstrated that the PCL is treated by O 2 or N 2 plasma, therby leading to hydrophilicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The contact angle method was used to understand the changes in surface wettability. Meghdadi et al (2019) reported an increase in the hydrophilicity of the cold atmospheric plasma-treated Poly (Ɛ-caprolactone) (PCL) surface using the water contact angle measurement [12].…”
Section: Discussionmentioning
confidence: 99%
“…Water contact angle. To measure the wettability of the surface, the static water contact angles (θ) were determined by the drop method at room temperature [12]. A droplet (5 μl) of water was placed on the untreated and 150 s helium plasma-treated on the defined surface area.…”
Section: Methodsmentioning
confidence: 99%